Mechanisms of mutant SOD1 induced mitochondrial toxicity in amyotrophic lateral sclerosis - Vehviläinen, Piia; Koistinaho, Jari; Gundars, Goldsteins (Frontiers in Cellular Neuroscience, 2014)
In amyotrophic lateral sclerosis (ALS), mitochondrial dysfunction is recognized as one of the key elements contributing to the pathology. Mitochondria are the major source of intracellular reactive oxygen species (ROS). Increased production of ROS as well as oxidative damage of proteins and lipids have been demonstrated in many models of ALS. Moreover, these changes were also observed in tissues of ALS patients indicative of important role for oxidative stress in the disease pathology. However, the origin of oxidative stress in ALS has remained unclear. ALS linked mutant Cu/Zn-superoxide dismutase 1 (SOD1) has been shown to significantly associate with mitochondria, especially in the spinal cord. In animal models, increased recruitment of mutant SOD1 (mutSOD1) to mitochondria appears already before the disease onset, suggestive of causative role for the manifestation of pathology. Recently, substantial in vitro and in vivo evidence has accumulated demonstrating that localization of mutSOD1 to the mitochondrial intermembrane space (IMS) inevitably leads to impairment of mitochondrial functions. However, the exact mechanisms of the selectivity and toxicity have remained obscure. Here we discuss the current knowledge on the role of mutSOD1 in mitochondrial dysfunction in ALS from the novel perspective emphasizing the misregulation of dismutase activity in IMS as a major mechanism for the toxicity.